Stock Control-Based Personal Protective Equipment Inventory System for Work Safety - Komang Yuli Santika; Putu Chrisdayanti Suada Putri; Luh Verra Sridyantari; Komang Drei Bayu Anggara; Putu Adi Guna Permana; Nyoman Sarasuartha Mahajaya (bit-Tech, 2026)
Effective management of Personal Protective Equipment (PPE) is crucial for ensuring worker safety in hazardous environments. However, manual PPE management often leads to issues, such as discrepancies between recorded stock and actual quantities and challenges in tracking tool distribution. As a result, there is a need for an inventory system that can effectively monitor and control PPE stock levels. This research aims to design a web-based inventory system capable of managing PPE with integrated stock control using the Economic Order Quantity (EOQ), Safety Stock, and Reorder Point (ROP) methods. The methodology used in this study is a Research and Development (R&D) approach with a prototyping model. The research includes the design of data structures and system process flows, as well as the implementation of key features, including a dashboard, inventory management, and PPE distribution. The data used consists of employee data, supplier information, PPE types, and existing stock, all of which are analyzed to support the stock control system. The results show that the developed system can record and monitor PPE stock levels more systematically than manual methods. Additionally, the system allows for accurate monitoring of PPE distribution to employees. In conclusion, the web-based PPE inventory system can significantly improve stock management efficiency and support workplace safety by ensuring the timely availability of appropriate PPE. Future research is recommended to test the system with real operational data and assess its impact on managing occupational safety risks.